2020
DOI: 10.1029/2020ja028551
|View full text |Cite
|
Sign up to set email alerts
|

On the Type‐A and Type‐B 150‐km Radar Echoes

Abstract: Type-A (weaker and wider Doppler spectra) and Type-B (stronger and narrower Doppler spectra) echoes are inherent to the puzzling 150-km echoing phenomenon. In this paper, we investigate the characteristics and possible origin of the Type-A and Type-B 150-km echoes using high-resolution 53-MHz radar and Digisonde observations from Gadanki. Results show that the Type-A echoes dominate the echoing phenomenon and they always precede the Type-B echoes. Intriguingly, the Type-B echoes are fundamentally not narrower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(59 reference statements)
2
6
0
Order By: Relevance
“…This is consistent with observations of 150 km echoes, which have been show to have more backscattered power for 30 MHz radars than 50 MHz (A. A. K. Patra et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with observations of 150 km echoes, which have been show to have more backscattered power for 30 MHz radars than 50 MHz (A. A. K. Patra et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…There are two populations of 150 km echoes, Naturally Enhanced Incoherent Scatter (NEIS), or Type-A, which have a typical signal-to-noise ratio (SNR) of around 5 dB, and Field Aligned Irregularities (FAIs), or Type-B, which can have a SNR of around 20 dB (Chau & Kudeki, 2013;A. K. Patra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In cases where larger volumes (beam width and range resolution) are used (e.g., over Gadanki), the resulting spectra might be a convolution of both type of echoes occurring at different altitudes. Patra et al (2020b) have shown that a simple moment method could be misleading on such occasions and suggested a classification considering also the frequency spread of the echoes. Perhaps a two-Gaussian fitting procedure would be more appropriate under these circumstances, i.e., one for the narrow spectral region with large amplitude and one for the wider region with less amplitude.…”
Section: Types Of Echoes Seasonal and Solar Variabilitymentioning
confidence: 99%
“…Previous to the aforementioned modeling and theory developments invoking photoelectrons, a variety of qualitative arguments were provided to try to explain different features of 150-km echoes. Based on the minute-scale temporal structures (Obs04) local and non-local neutral gravity waves at different scales have been invoked (e.g., Røyrvik, 1982;Kudeki and Fawcett, 1993;Patra, 2011;Patra et al, 2020b). Their contributions have been qualitatively attributed to: (a) modulating N e , creating significant density gradients and depletions, and (b) providing strong shears in the neutral wind.…”
Section: Other Considerationsmentioning
confidence: 99%
“…The type A is associated with NEIS process in which the spectral width is proportional to that of signal-to-noise ratio (SNR), and the type B is related with FAIs in which the spectral width is very small regardless of SNR (Patra 2011;Chau and Kudeki 2013;Patra and Chaitanya 2016). On the other hand, Patra et al (2020) proposed that both types of echoes are primarily of common origin linked with the NEIS process and atmospheric gravity waves play an important role in driving the 150-km echoes as originally proposed by Kudeki and Fawcett (1993). Recent high-resolution observation by the Jicamarca VHF radar revealed that the 150-km echoes were likely modulated by gravity waves (Reyes et al 2020), whereas it does not mean that gravity waves play a critical role in generation of 150-km echoes.…”
mentioning
confidence: 99%